Anosmia as presenting symptom in COVID-19 patients - Dafallah, Mumen Abdalazim; Ragab, Esraa Ahmed; Ragab, Salma A. (International Journal Of Community Medicine And Public Health, 2020)
Corona virus disease 2019 is characterized predominantly by lower respiratory tract involvement, but also caused extra pulmonary manifestations. Recently, anosmia emerged as an important symptom in this pandemic. The report clarifies the importance of this issue. The data was searched in pub Med, Medline and Google scholar. A total of 227 articles were initially identified, however 36 important articles were chosen for full reading. Anosmia observed to appear in the early course of the disease and could be the initial and/or the only presenting symptom. It occurred more commonly among female and young age patients, and associated significantly with dysgeusia. The study showed that recovery from anosmia is likely in the majority of cases. We conclude that anosmia proved to be an important symptom in COVID-19 and used as tool for screening.